The effect of acetone as a post-production finishing technique on entry-level material extrusion part quality - Havenga, S.P.; De Beer, D.J.; Van Tonder, P.J.M.; Campbell, R.I. (South African Journal of Industrial Engineering, 2018)
Entry-level material extrusion artefacts persistently suffer from questionable weakened end-product production quality, according to industrial standards. These limitations can be addressed by the development of improved finishing techniques that may narrow the gap between low-cost and high-end production methods in additive manufacturing. In doing so, the technology may become available to a larger spectrum of prosumers who previously were reluctant to use entry-level technology because of these limitations. This article describes the effect that acetone has as a post-production finishing technique for low-cost artefact production. Through a series of quantitative investigations, the study provides evidence that acetone reduces the tensile strength, increases polymer ductility, and significantly reduces the surface profile roughness of thermoplastics such as acrylonitrile butadiene styrene. The potential cost and waste reduction for entry-level manufactured products can then be identified. Intreevlak materiaal ekstrusie modelle word tans, volgens industriële standaarde, deur verswakte eindproduk produksie-kwaliteit benadeel. Hierdie tekortkominge kan deur die ontwikkeling van verbeterde afwerkingstegnieke aangespreek word. Sodoende kan die gaping tussen intree- en hoë-vlak laagvervaardiging vernou word. Meer gebruikers wat voorheen onwillig was om die tegnologie as gevolg van tekortkominge te gebruik, kan nou toegang verkry daartoe. Die artikel bespreek die impak wat asetoon as post-produksie afrondingsmiddel vir lae-koste produksie kan bewerkstellig. Deur ’n reeks kwantitatiewe ondersoeke bewys die artikel dat asetoon die treksterkte van akrylonitrilbutadienestyrene (ABS) verswak, die polimeriseer-baarheid daarvan versterk, en die oppervlak profiel ruheid drasties verminder. Potensiële koste en afvalvermindering kan dus hierdeur vir intreevlak vervaardigde produkte geïdentifiseer word.